THE PROPAGATION OF UNCERTAINTY SHOCKS: ROTEMBERG VERSUS CALVO - Joonseok Oh (International Economic Review, 2020)
This article studies the effects of uncertainty shocks on economic activity, focusing on inflation. Using a vector autoregression, I show that increased uncertainty has negative demand effects, reducing GDP and prices. I then consider standard New Keynesian models with Rotemberg-type and Calvo-type price rigidities. Despite the belief that the two schemes are equivalent, I show that they generate different dynamics in response to uncertainty shocks. In the Rotemberg model, uncertainty shocks decrease output and inflation, in line with the empirical results. By contrast, in the Calvo model, uncertainty shocks decrease output but raise inflation because of firms' precautionary pricing~motive.
Keywords: 330